Long-term safety of combination treatment with methotrexate and tumor necrosis factor (TNF)-α antagonists versus TNF-α antagonists alone in psoriatic patients - Hoffmann, Jochen; Knoop, Christian; Schäkel, Knut; Enk, Alexander; Hadaschik, Eva (The journal of dermatology, 2021)
Methotrexate, a folic acid analog, is the conventional systemic anti-psoriatic agent most commonly chosen for combination with biologics in the treatment of psoriasis. Real-world long-term safety data of this combination versus biologic treatment alone in dermatological practice are sparse.